„Aber viel wichtiger, ich hoffe, nicht.“: Funktion und Relevanz beruflicher Nutzung von digitalen Plattformen durch fortgeschrittene Musikstudierende - Herr, Corinna; Wernicke, Carsten (Die Musikforschung, 2024)
Music students and music academies face challenges from the demands of an increasingly digitised practice environment as well as from the changing professional image of musicians. Through interviews and a focused netnography, this qualitative exploratory study (which involved six advanced music students at two conservatoires) examines the relevance that advanced music students ascribe to the use of social media, exploring in particular which practices seem relevant and feasible to them. The study also explores the extent to which the music students distinguish between private and public online personas. A first attempt at typologising shows that the music students have developed different attitudes towards the use of social media, which can be positioned between the extremes of conservative and affirmative manifestations. The educational institutions are considered by their students as playing an ambivalent role, both as facilitators and as obstacles in the implementation of digital self-presentation strategies.